Accountability dalam Pendidikan Islam: Teori, Konsep, dan Implikasinya dalam Manajemen Pembiyaan - Mustofa Fathurrahman, Iqbal; Ahmad Hafiidhy, Luthfi; Juanda; Patonah; Hadiatati, Eti (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Accountability in Islamic education is a crucial aspect in ensuring transparent, efficient, and accountable financing management. The background of this study is the gap between accountability theory and financial management practices in Islamic educational institutions that are still not optimal. The purpose of this study is to analyze the theory and concept of accountability and examine its implications in the practice of Islamic educational financing management. The main problem in this study is how the implementation of accountability can strengthen the governance of financing in Islamic educational institutions. The method used is a qualitative approach based on literature studies and literature analysis from accredited scientific journals, combined with case studies in several Islamic educational institutions. The results of the study indicate that the implementation of accountability principles such as transparency, participation, and accountability is very influential in increasing public trust and the effectiveness of the use of educational funds. This study concludes that accountability based on Islamic values ​​can be used as a foundation for strengthening sustainable education financing management.